2006
DOI: 10.1111/j.1365-2753.2006.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to surgical and radiation treatment guidelines in relation to patient outcome in early stage endometrial cancer

Abstract: This suggests that extensive surgical procedures are redundant in the treatment of occult stage II endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…20,22 In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient noncompliance for postoperative radiotherapy and survival. [23][24][25][26][27][28][29] Our results of decreased survival in non-compliant women with endometrial cancer for postoperative radiotherapy are consistent with past studies reporting decreased survival related to non-compliance to radiotherapy shown in other malignancies. 6,7,29 Therefore, our study not only validates their results but also endorses that patient compliance for radiotherapy is an important factor for prognosis of women with endometrial cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20,22 In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient noncompliance for postoperative radiotherapy and survival. [23][24][25][26][27][28][29] Our results of decreased survival in non-compliant women with endometrial cancer for postoperative radiotherapy are consistent with past studies reporting decreased survival related to non-compliance to radiotherapy shown in other malignancies. 6,7,29 Therefore, our study not only validates their results but also endorses that patient compliance for radiotherapy is an important factor for prognosis of women with endometrial cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Both the care provider‐side and the patient‐side can be factored for the guideline adherence, and these possible guideline adherent factors include hospital volume, patient medical comorbidities, and patient non‐compliance . In endometrial cancer, prior studies mainly examined guideline adherence to surgical treatment recommendation or mixed with other malignancies, and no study has solely examined the association of patient non‐compliance for postoperative radiotherapy and survival …”
Section: Discussionmentioning
confidence: 99%
“…LND in intermediate/high-risk EC has been also studied in numerous retrospective trials, showing controversial results in relation to its survival benefit [ 22 23 ]. Our group recently performed a retrospective matched pair study, which included 194 (97 pairs) diagnosed of high-risk EC, finding no benefit in DFS and OS of LND [ 10 ].…”
Section: Disccussionmentioning
confidence: 99%
“…LND in intermediate/high-risk EC has been also studied in numerous retrospective trials, showing controversial results in relation to its survival benefit [22,23]. Our group recently performed a retrospective matched pair study, which included 194 (97 pairs) diagnosed of high-risk EC, finding no benefit in DFS and OS of LND [10].…”
Section: Disccussionmentioning
confidence: 99%